Generation of intense ultra-short X-ray pulses in wake field undulator - Opanasenko, A. (Вопросы атомной науки и техники, 2011)
The generation of X-rays based on the interaction mechanism of a relativistic charged particles with alternative wake fields induced in periodic structures are studied. The optimum wake field characteristics providing the maximum flux of wake field undulator radiation in an X-ray range are obtained. Using the data on beam parameters of varied photo-injector projects, the X-ray fluxes are calculated.